Structuring Supplier Involvement in New Product Development: A China–U.S. Study. (17th December 2015) - Yan, Tingting; Nair, Anand
ABSTRACT: Buying and supplying organizations rely on each other for developing better products in an efficient manner, which explains the popularity of involving suppliers in new product development (NPD). However, such involvement is not always successful, partially due to the challenges of structuring a buyer–supplier team to manage joint dependence and dependence asymmetry. This study adopts an organizational dependence view to examine how three types of intergroup structures—administrative (formalization and centralization), task (task interdependence), and physical (colocation)—influence project performance and buyer learning in NPD projects. Furthermore, adopting a contingency theory perspective, we study whether the national context moderates the effects of intergroup structures on project outcomes. We adopt a two‐group structural equation modeling approach to test hypotheses with survey responses from a sample of NPD projects in the United States (US) and China. Results show different ways in which intergroup structures influence project performance and buyer learning in the two culturally, economically, and institutionally distinct countries. We discuss the implications of these new findings and present directions for future research.